Hierarchical multi-scale microstructural evolution in an as-cast Al2CuCrFeNi2 complex concentrated alloy. (April 2016) - Borkar, T.; Gwalani, B.; Choudhuri, D.; Alam, T.; Mantri, A.S.; Gibson, M.A.; Banerjee, R.
Abstract: The hierarchical evolution of the microstructure in an as-cast Al2 CuCrFeNi2 alloy, across multiple length scales, was investigated by coupling scanning and transmission electron microscopy and atom probe tomography. This cast alloy undergoes a univariant eutectic dendritic solidification, which gives rise to a two-phase mixture of B2e (ordered BCC) and βe (disordered BCC) phases. The B2e phase forms a continuous matrix with the βe, being the minor phase, having a rod-like morphology. The B2e phase is further decomposed into B2f, Cu-plates, Cu-globules, and a small volume fraction of (Fe, Cr)-rich disordered βf2 regions. The βe phase further decomposed into Cu/B2s core/shell composite particles, where an ordered B2s shell surrounds a Cu-rich core. Most likely these Cu-rich cores act as heterogeneous nucleation sites for the B2s precipitates within the βf phase. This complex multi-scale decomposition process results in an intricate mixture of ordered and disordered solid solution phases. Highlights: Hierarchical Multi-scale Microstructural Evolution observed in high entropy alloys. Eutectic dendritic solidification leads to ordered and disordered BCC phases. Microstructure consisted of Fe–Cr rich: BCC and Ni–Al rich: B2 phases. The disordered BCC regions exhibit Cu-rich core and B2 as the surrounding shell.